Paleocurrent Analysis of the Early Pliocene Nagri Formation, Southern Kohat Plateau, Sub Himalayas, Pakistan: Paleocurrent of the Nagri Formation (Biological Sciences - PJSIR, 2010)
The present study is based on the paleocurrent analysis of sandstone of the Early Pliocene Nagri Formation, exposed in the southern limb of Shahbazgarh Syncline, Shahbazgarh area, southern Kohat Plateau, sub Himalayas, Pakistan. The readings of paleocurrents were taken from the cross beds of the sandstone by following a traverse of one and a half kilometer along the strike of formation. The analysis of data and its graphical presentation indicated that the orientation of paleostreams and direction of their paleocurrents was north 30° east at the time of deposition of early pliocene Nagri formation. The paleo position of the Indo-Pakistani plate was in the north-east orientation during the pliocene. Based on the present study, it is concluded that the Himalayan Hinterland was the probable sediment source of the Nagri formation in the study area and the sediments were transported through paleostreams flowing in the north- east south-west orientation.